The Present Scientific Revolution on the Borderline between Physics and Biology - Ślósarek, Genowefa (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2012)
At the end of the 20th century, substantial changes in the paradigms of molecular physics and biology occurred. They have brought two new and entirely independent, fields of scientific research – nanotechnology and systems biology. Thanks to these disciplines, a new paradigm was born opening a new way of research in biology. It enables a holistic treatment of living organisms. As a consequence of these changes, an entirely new picture of the interface between physics and biology emerges.